A climbing robot with paired claws inspired by gecko locomotion. Issue 10 (8th October 2022) - Han, Qingfei; Ji, Aihong; Jiang, Nan; Hu, Jie; Gorb, Stanislav N.
Abstract: Climbing robots that use bionic claws can climb vertical or even inverted rough surfaces. However, wall-climbing robots with unidirectional spiny feet cannot crawl horizontally or downward on vertical rough surfaces. In this paper, a pair of gripping spiny feet is used to give a robot the capacity to crawl in any direction on a rough wall. On the basis of observations of the gecko's method for grasping onto a vertical rough surface, a multilevel interlocking structure is proposed. A spherical contact model of the claw tip on a vertical rough surface is established, and the influences of the contact angle, friction coefficient, and other factors on the grappling claw action are analyzed. Moreover, the optimal structure of the grappling claws is proposed. The force during the grasping and detachment of the mechanism and the influence of the number of feet on grasping performance are determined through experiments. Furthermore, a six-legged wall-climbing robot is designed and evaluated in terms of crawling on a vertical rough surface at various angles. The feasibility of using an opposed gripping mechanism to allow a robot to crawl in any direction on a vertical rough surface is also verified.